The Characteristics of Self-Reported Symptomatic by Individuals with Mild COVID-19 during Omicron Pandemic in China: Cross-Sectional Online Survey - Xiang Liu; Xiaoling Wei; Xiangju Xing; Ling Lu; Min Chen; Yumei Zhao; Shuang Zhou; Ting Feng; Li Wang; Chengling Luo; Jing Xia; Jun Zhang; et al. (International Journal of Clinical Practice)
Background. An outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic occurred throughout China from December 2022 to January 2023, and the vast majority of those infected individuals were mild. The symptom characteristics of mildly infected individuals in this epidemic wave of the Omicron variant have not been well described. Methods. We conducted a nationwide survey of symptomatic characteristics of nonhospitalized individuals with mild Omicron infection through a WeChat app. Results. Respondents (68.6% female) were aged 18–87 years (42.6 ± 13.1 years), of whom 79.8% were diagnosed by SARS-CoV-2 PCR or antigen test. Of the 19 symptoms predefined in the questionnaire, an average of 7.8 symptoms was reported. The most common symptoms included cough (81.2%), fever (79.9%), fatigue (73.8%), muscle soreness (62.2%), headache (59.2%), and phlegm (55.1%). Painful swallowing was present in 38.3% of the participants and was one of the most severe symptoms perceived by the participants. Also, we found that young people were more likely to have symptoms such as fever, painful swallowing, and headache compared to the elderly population. 36.9% of respondents graded their symptoms as severe, and the severity of symptoms was higher in young people than in older adults, with fever, cough, painful swallowing, fatigue, and headache being the most severe. In addition, women experienced a significantly higher prevalence of symptoms than men, but there was no significant difference in the severity of most symptoms. The presence of comorbidities did not increase the incidence or severity of symptoms in those with mildly infected individuals. Conclusions. The symptom profile of mild COVID-19 cases in the nationwide Omicron wave in China was markedly different from previous reports, featuring a high incidence of symptoms, multiple symptoms, and heavy symptoms. The symptoms of mild Omicron infection cases are not mild and are more pronounced in young people.